Matemática e cultura amazônica: representações do brinquedo de miriti - SANTOS, Ivamilton Nonato Lobato dos (Universidade Federal do Pará, 2013)
In the city of Abaetetuba-Pará there is a socio-economic practice of producing a local craft that has been consolidated as more a culture of Amazonian peoples. The 'toys miriti' as they are commonly known, are produced from a palm tree native to the Amazon, the miritizeiro (Mauritia flexuosa). Parts manufactured craft had its origin lost in time, but have maintained their tradition over the years by artisans who produce and market this craft, whose peak sales occur, first in June then in October, on the occasion of the Festival Miriti, in Abaetetuba, and the Candle of Nazareth, the capital Belém, respectively. These artisans, and reproduce in the toy scene in which Amazon daily living, demonstrate intent, invent and reinvent knowledge here understood as social representations. Thus, this study aims to analyze mathematical representations and heritage of craftsmanship present in miriti Abaetetuba; analyze parts, identifying school and non-school knowledge; analyze elements of cultural and environmental context that contemplate the environmental heritage education from the point of view of ethnographic , approaching the social, cultural and environmental aspects of mathematical relationships present in the toy miriti. The theoretical and methodological approach of this research is based on the Theory of Social Representations with ethnographic characteristics. Data were analyzed based on the discourse of artisans toy miriti. From Representations and conviviality with two groups of artisans - and ASAMAB MIRITONG-was perceived concern and respect for the environment by craftspeople in all stages of the production of handicrafts, missing a few tweaks to make this sustainable practice. The know-how of artisans is filled with culture and knowledge passed on informally and peculiar characteristic of the Environmental Heritage Education. Mathematical elements identified in parts, procedures and representations, are in some cases consistent with discusses in ethnomathematics.